2022
DOI: 10.1039/d2na00461e
|View full text |Cite
|
Sign up to set email alerts
|

Packing and trimer-to-dimer protein reconstruction in icosahedral viral shells with a single type of symmetrical structural unit

Abstract: Understanding the principles of protein packing and the mechanisms driving morphological transformations in virus shells (capsids) during their maturation can be pivotal for the development of new antiviral strategies. Here,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…Using recent structural data on both shells of the immature Zika virus, 9 we calculated the protein charges as a function of pH based on the simple Henderson-Hasselbalch isotherm and the corresponding energy of electrostatic interactions in the virus. By comparing our results with the ones previously obtained for the dengue virus, 58 we found that the pH-dependent changes of electrostatic interactions between constituting proteins can contribute to the driving mechanism of the transformation, which is also assisted by an increase in the attraction of positively charged heterodimers to a negatively charged interposed lipid bilayer membrane of flaviviruses.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Using recent structural data on both shells of the immature Zika virus, 9 we calculated the protein charges as a function of pH based on the simple Henderson-Hasselbalch isotherm and the corresponding energy of electrostatic interactions in the virus. By comparing our results with the ones previously obtained for the dengue virus, 58 we found that the pH-dependent changes of electrostatic interactions between constituting proteins can contribute to the driving mechanism of the transformation, which is also assisted by an increase in the attraction of positively charged heterodimers to a negatively charged interposed lipid bilayer membrane of flaviviruses.…”
Section: Discussionsupporting
confidence: 68%
“…3b demonstrates that in the trimeric state, at pH < 6.6, the electrostatic interactions between heterodimers tend to destabilize the surface of the DENV and the immature dimeric state becomes more energetically favorable. As we have shown in our previous work, 58 upon pH-induced 3C6D → 3C6R transition, the electrostatic energy of the outer shell is significantly reduced due to the relocation of negatively charged pr peptides, which are grouped into three peptides in the trimeric state and shift to almost equidistant positions in the dimeric structure (see Fig. 2a and c), and this drastically decreases the repulsive forces between them.…”
Section: Ph-induced Structural Changes In Flavivirus Shells During Th...supporting
confidence: 69%
“…Changes in pH of the bathing solution can lead specifically to substantial changes in electrostatic charge of the viral proteins 31 that can in its turn drive global structural rearrangements of protein assemblies. 32,33 Motivated by the experimental findings 4,14,34 that disassembly of Cypovirus polyhedra and release of the embedded virions are strongly dependent on the acidity of the surrounding solution, we now examine the molecular details of how the increase in pH affects interactions between viral proteins and polyhedrin trimers.…”
Section: Resultsmentioning
confidence: 99%
“…Standardly the screening length under physiological conditions can be estimated to be l D z 1 nm. 32,33,41 First, let us discuss how the trimer charge and electrostatic energy of CPV1 polyhedrin crystal (5GQL) change with the increasing pH. Fig.…”
Section: Electrostatic Mechanism Of the Virus Superstructure Disassemblymentioning
confidence: 99%
See 1 more Smart Citation